Pengaruh Bokashi Limbah Kulit Kopi pada Bibit Pepaya (Caraca Papaya L.) Calina - Hadisfied Rama Suhada; Umi Trisnaningsih; Siti Wahyuni (Jurnal Ilmu Pertanian Indonesia, 2024)
This study aimed to determine the effect of the proportion of coffee peel bokashi in the planting medium on the growth of papaya plant seedlings (Carica papaya L.) cv Calina. The research was conducted at the Faculty of Agriculture Screenhouse on Jalan Perjuangan, Cirebon City, at an altitude of 5 m above sea level. The research was conducted from May 2022 to June 2022. The experimental method used with a completely randomized design. The treatment consisted of 4 proportions of bokashi in the planting media, each of which was repeated 6 times so that there were 24 experimental units. Each experimental unit consisted of 10 polybags. The total papaya plant seeds used were 240 seeds. The treatments studied were: K0 = top soil, K1 = 250 g bokashi + 1 kg soil, K2 = 500 g bokashi + 1 kg soil, and K3 = 750 g bokashi + 1 kg soil. The results showed that the proportion of coffee peel waste bokashi significantly affected the growth of papaya plants. Using 500 g coffee skin waste bokashi in 1 kg of soil had the best effect on plant height, stem diameter, plant growth rate, number of leaves, root volume, root length, root ratio, and net assimilation rate. Keywords: coffee peel, bokashi, papaya